Exploring the Impact of Rabbani Character Values on Learning Outcomes in Prospective Elementary Education Teachers - Suriana Suriana; Nuraini Nuraini; Lisa Lisa (STAI Hubbulwathan Duri, 2024)
Instilling Rabbani character values in prospective Madrasah Ibtidaiyah teachers is crucial, as it ensures that they not only possess cognitive intelligence but also excel in the affective domain, fostering profound spiritual intelligence. This holistic development can be achieved through the learning process, including mathematics education. This study utilized a mixed-method approach with a sequential explanatory design and was conducted at IAIN Lhokseumawe and IAIN Langsa. These institutions, located in the northern and eastern parts of Aceh Province near North Sumatra, exhibit differences in religious values, culture, and character. The sample consisted of 81 respondents, including 38 students from IAIN Lhokseumawe and 41 students from IAIN Langsa. Data collection methods included learning outcomes tests and questionnaires to assess the Rabbani character values of students. Data analysis was performed using the Rank-Spearman correlation with SPSS 26, yielding a significance value (2-tailed) of 0.0000.05. The regression analysis results indicated that Rabbani character values accounted for 12.8% of the variance in learning outcomes. This finding underscores the significant impact of these character values on enhancing the mathematics learning outcomes of prospective Madrasah Ibtidaiyah teachers.